Outcome of chiropractic therapy in idiopathic scoliosis – a preliminary study / Syahirah Zeti Azham … [et al.] - Azham, Syahirah Zeti; Kamaruddin, Nur Firzanie; Sallehudin, Lyanna Annura; Haron, Mohd Nizam; Rozali, Khairul Nizam; Sidek, Sabrilhakim (Universiti Teknologi MARA Cawangan Selangor, 2017)
The purpose of this study is to retrospectively report the results of scoliosis patients who underwent chiropractic therapy and to evaluate their outcome by looking at the potential to alter the natural progression of scoliosis after therapy. Methods: Retrospective data collection was conducted at a private chiropractic centre in Kuala Lumpur. The data was collected from patients between the ages of 16 to 19 years old. A total of eight patients with 14 scoliotic curvatures (six thoracic, six lumbar and two thoracolumbar), who met the inclusion criteria, were selected as subjects for this study. All subjects received the same chiropractic therapy program. The outcome of the therapy was assessed by measuring the Cobb’s angle on the erect spine as captured on an x-ray. The Cobb’s angle was measured at the first presentation (to establish a baseline) after 6 and 24 months of therapy. Results: The mean baseline Cobb’s angle for thoracic, lumbar and thoracolumbar scoliosis were 30.7o ± 19.4o , 31.7o ± 12.3o and 25.0o ± 18.4o respectively. After 24 months of chiropractic therapy, there was no discernible effect on the magnitude of the Cobb’s angles on the subjects overall. Conclusion: Our study showed no significant reduction in spine curvature in patients with scoliosis using chiropractic therapy after 24 months.